MARKETING MANAGEMENT IN THE MANAGEMENT SYSTEM OF A BANKING INSTITUTION - BLAHUN, Ivan; GRYNEVYCH, Liudmyla (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article deals with the introduction of software into the bank’s business process. Marketing management plays an important role in the management system of a banking institution. Yes, this is especially evident in his marketing activities. Constant competition in the banking sector creates the need to find new forms of influence on bank clients. To do this, it is necessary to understand the strengths of the bank-competitor and to form its own marketing development strategy accordingly. Marketing research is precisely the tool that allows you to collect, analyze and determine the directions of development of a banking institution. The main factor in this process is time. The faster and in full all the necessary information is received, the more chances there are to make a balanced management decision that will allow you to win in the competition. Therefore, the transformation of the business process due to the introduction of software becomes a significant advantage that allows you to get a positive effect from such actions. The article provides a comparative analysis of the use of traditional classical methods for marketing research with software products that can be used in the activities of a banking institution to conduct marketing research of the competitive environment of the banking sector and evaluate its strategic alternatives. The use of SWOT analysis in the process of marketing research has a number of advantages, but also significant disadvantages: the duration of processing the obtained results in time and the laboriousness of such work. To solve this problem, it is advisable to implement an information system such as a CRM system, which is a system for collecting and analyzing data from all channels of the bank’s activity. Such software products include: NetHunt, KeepinCRM, KeyCRM. These services specialize in collecting data from CRM systems, advertising platforms and sites, help to find inefficient traffic channels and save advertising budget, attract more traffic, increase conversion into applications, increase sales and customer loyalty. The main advantage of these systems is their analytical and visibility, which in the complex contributes to the adoption of a balanced management decision.